Asian Regional Development Strategies: A Case Study of ASEAN Plus Three (APT) - Nasution, Muhammad Imam Syaamil; Cahyani Muis, Afni Regita (Global and Policy Journal of International Relations, 2024)
ABSTRACT In recent decades, Asia has emerged as a pivotal hub of global economic growth, with rapid economic expansion evident across the region. This paper explores the effectiveness of the ASEAN Plus Three (APT) framework, comprising the ten ASEAN member states along with China, Japan, and South Korea, in driving regional economic development through import substitution, export-led growth, and structural adjustment strategies. The analysis highlights significant advancements in regional economic integration and infrastructure development, supported by robust data demonstrating the region's dynamic transformation. Before the implementation of APT strategies, ASEAN Plus Three countries exhibited varying levels of economic performance, with GDP growth rates averaging 4.2% across the region, contrasted with a global average of 2.8% (IMF, 2023). Post-implementation data reveals a notable increase, with regional GDP growth reaching 5.3% in 2022, surpassing the global average and demonstrating the impact of APT strategies (IMF, 2023). The study employs a comparative analysis of three key case studies: regional economic integration, infrastructure development, and food and energy security. Results indicate that intra-regional trade has increased significantly, contributing to over 30% of total regional trade by 2021 (ASEAN Secretariat, 2022). This paper underscores the critical role of APT in enhancing economic stability and development within the Asian region. It provides policy recommendations for strengthening regional cooperation and addressing challenges such as income disparities and structural imbalances. Future research could further investigate the nuanced impacts of APT's strategies on individual member states and explore the long-term sustainability of these development approaches. Keywords: ASEAN Plus Three, Economic Development, Import Substitution, Export-Led Growth, Structural Adjustment, Regional Integration ABSTRAK Dalam beberapa dekade terakhir, Asia telah muncul sebagai pusat pertumbuhan ekonomi global yang penting, dengan ekspansi ekonomi yang pesat di seluruh wilayah. Makalah ini mengeksplorasi efektivitas kerangka ASEAN Plus Three (APT), yang terdiri dari sepuluh negara anggota ASEAN bersama dengan Cina, Jepang, dan Korea Selatan, dalam mendorong pembangunan ekonomi regional melalui substitusi impor, pertumbuhan berbasis ekspor, dan strategi penyesuaian struktural. Analisis ini menyoroti kemajuan signifikan dalam integrasi ekonomi regional dan pengembangan infrastruktur, didukung oleh data kuat yang menunjukkan transformasi dinamis di kawasan ini. Sebelum penerapan strategi APT, negara-negara ASEAN Plus Three menunjukkan tingkat kinerja ekonomi yang bervariasi, dengan rata-rata pertumbuhan PDB sebesar 4,2% di kawasan ini, dibandingkan dengan rata-rata global sebesar 2,8% (IMF, 2023). Data pasca-implementasi menunjukkan peningkatan signifikan, dengan pertumbuhan PDB regional mencapai 5,3% pada tahun 2022, melampaui rata-rata global dan menunjukkan dampak positif strategi APT (IMF, 2023). Studi ini menggunakan analisis komparatif dari tiga studi kasus utama: integrasi ekonomi regional, pengembangan infrastruktur, serta ketahanan pangan dan energi. Hasilnya menunjukkan bahwa perdagangan antarwilayah telah meningkat secara signifikan, menyumbang lebih dari 30% dari total perdagangan kawasan pada tahun 2021 (Sekretariat ASEAN, 2022). Makalah ini menekankan peran penting APT dalam meningkatkan stabilitas dan perkembangan ekonomi di kawasan Asia, serta memberikan rekomendasi kebijakan untuk memperkuat kerja sama regional dan mengatasi tantangan seperti ketimpangan pendapatan dan ketidakseimbangan struktural. Penelitian di masa depan dapat lebih mendalami dampak spesifik strategi APT terhadap masing-masing negara anggota dan mengeksplorasi keberlanjutan jangka panjang pendekatan pembangunan ini. Kata Kunci: ASEAN Plus Three, Pembangunan Ekonomi, Substitusi Impor, Pertumbuhan Berbasis Ekspor, Penyesuaian Struktural, Integrasi Regional